The Emerging Roles of Endocrine Hormones in Different Arthritic Disorders - Eugenia Bertoldo (Frontiers in Endocrinology, 2021)
The relationship between endocrine hormones and the spectrum of rheumatic conditions has long been discussed in the literature, focusing primarily on sexual hormones, such as estrogens, androgens, prolactin (PRL). Estrogens are indeed involved in the pathogenesis of the main inflammatory arthritis thanks to their effects on the immune system, both stimulatory and inhibitory. The PRL system has been discovered in synovial tissue of rheumatoid arthritis (RA) and psoriatic arthritis (PsA), patients and has been propose as a new potential therapeutic target. Besides sexual hormones, in the last years scientific interest about the crosstalk of immune system with other class of hormones has grown. Hormones acting on the bone tissue (i.e. parathyroid hormone, vitamin D) and modulators of the Wnt pathway (i.e. Dickkopf-1) have been demonstrated to play active role in inflammatory arthritis course, defining a new field of research named osteoimmunology. PTH, which is one of the main determinants of Dkkopf-1, plays a crucial role in bone erosions in RA and a correlation between PTH, Trabecular Bone Score (TBS) and disease activity has been found in ankylosing spondylitis (AS). In PSA is under studying the interaction among IL-17 and bone metabolism. The purpose of this review is to discuss and summarize the recent data about the interaction between endocrine hormone and immune system in the main rheumatic disorders, covering in particular the role of bone-related hormones and cytokines. We will describe this relationship from a biochemical, diagnostic and therapeutic perspective, with a particular focus on RA, PsA and AS.